2021
DOI: 10.1038/s41598-021-86789-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing fatty acid-induced lipotoxicity and its therapeutic potential in glioblastoma using stimulated Raman microscopy

Abstract: Glioblastoma multiforme (GBM) is the most aggressive primary brain tumor. The effectiveness of traditional therapies for GBM is limited and therefore new therapies are highly desired. Previous studies show that lipid metabolism reprogramming may be a potential therapeutic target in GBM. This study aims to evaluate the therapeutic potential of free fatty acid-induced lipotoxicity for the suppression of glioma growth. U87 glioma cells are treated with three fatty acids (FAs): palmitic acid (PA), oleic acid (OA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…Lipid droplets (LDs) are organelles that are commonly found in fatty tissues storing lipids, triglycerol, and cholesterol esters. Recently, the presence of LDs has been demonstrated in glial and glioblastoma cell cultures in vivo [73]. These LDs are not only a simple reservoir of fatty acids but have an impact on important cell processes such as cell cycles, cell migration of glial cells, and their resistance to apoptosis and conventional treatments [69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid droplets (LDs) are organelles that are commonly found in fatty tissues storing lipids, triglycerol, and cholesterol esters. Recently, the presence of LDs has been demonstrated in glial and glioblastoma cell cultures in vivo [73]. These LDs are not only a simple reservoir of fatty acids but have an impact on important cell processes such as cell cycles, cell migration of glial cells, and their resistance to apoptosis and conventional treatments [69].…”
Section: Discussionmentioning
confidence: 99%
“…It has been established for a long time [75] that GBM diverts brain lipid metabolism to its advantage to sustain the energy stores needed for their own expansion. By focusing on these LDs, it has been shown that they play a central role in this lipid metabolism reprogramming [73]. Furthermore, it has been reported that autophagy-mediated hydrolysis of these LD maintains energy homeostasis [76].…”
Section: Discussionmentioning
confidence: 99%
“…Upon entering the glioma cell, PA can be dedicated to various pathways, including beta-oxidation, membrane lipid production, or sphingolipid biosynthesis. However, excess PA accumulation induces lipotoxicity in T98G [ 42 ] and U87 GBM cells [ 43 ] by triggering the formation of ROS and promoting the ER stress pathways [ 42 ]. This can ultimately lead to apoptosis at PA concentrations greater than 300 μM [ 42 , 43 ].…”
Section: Palmitic Acid Uptake and Incorporation Into The Sphingolipid...mentioning
confidence: 99%
“…[5] In biomedical research, Raman spectroscopy has emerged as a novel technique in measuring the chemical composition and molecular structure of cells and tissues. [6][7][8][9][10] Molecular changes are reflected in the spectra of diseased tissues, compared to those of the healthy ones, and are recognized as biochemical markers of the ex vivo and in vivo diseases. [8,[11][12][13][14] Fatty acids of lipid droplets (LDs) are recognized as biochemical markers in cancer cells and liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%